Rural Education as a tool in facing coloniality in Brazil - Pacheco, Júlio César de Almeida; Ribeiro, Luiz Paulo; Almada, Emmanuel Duarte (Revista Cerrados, 2022)
The Brazilian rural landscape has been constituted through historical tensions that had repercussions on our entire social organization as a country. This landscape was structured following coloniality-based approach, which set the social place where Latin American peasants and territories were positioned. The objective of this essay is, thus, to discuss the relationship between Rural Education and the confrontation of coloniality. Methodologically, we start from a critical reading of the theoretical production on coloniality and Rural Education in Latin America, focusing on the intersections and crossings between these two theoretical-political fields in the Brazilian historical and territorial context. The struggle for the right to education brought the affirmation of rural landscapes as the territory of people’s rights, opposing the coloniality that marginalized, through its modern rationality, the non-white peoples and the rural territories. This is the main aspect of disputes brought by Rural Education. It struggles for access to education, however, associated with other civil rights that demand a new social, political, cultural, and economic placement of rural peoples and their territories. Rural Education reshapes the Brazilian project of country and society project, taking into account the relevance of rural peoples in its constitution and, therefore, becomes the resistance to coloniality that has historically structured Latin American societies.